2016
DOI: 10.1111/bpa.12412
|View full text |Cite
|
Sign up to set email alerts
|

On the distribution of intranuclear and cytoplasmic aggregates in the brainstem of patients with spinocerebellar ataxia type 2 and 3

Abstract: The polyglutamine (polyQ) diseases are a group of genetically and clinically heterogeneous neurodegenerative diseases, characterized by the expansion of polyQ sequences in unrelated disease proteins, which form different types of neuronal aggregates. The aim of this study was to characterize the aggregation pathology in the brainstem of spinocerebellar ataxia type 2 (SCA2) and 3 (SCA3) patients. For good recognition of neurodegeneration and rare aggregates, we employed 100 µm PEG embedded brainstem sections, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 48 publications
0
37
0
Order By: Relevance
“…Previous studies have shown that p62 localizes to protein aggregates in many neurodegenerative diseases including SCA3 and may play a protective role in autophagic clearance of polyglutamine disease proteins. 28,29,41,42 By immunoblot analysis, diencephalic and cerebellar p62 expression levels did not differ across vehicle-treated WT, vehicle-treated Q84/Q84, or ASO-5-treated mice (see Fig 7C, E, F, H). We did, however, observe small, nuclear p62-positive puncta in the pons of Q84/Q84 vehicle-treated mice at 16 weeks of age, which were nearly absent in vehicle-treated WT or ASO-5-treated Q84/Q84 mice (see Fig 7B).…”
Section: Aso-5 Reverses Slowed Firing Frequency In Sca3 Purkinje Neuronsmentioning
confidence: 84%
See 3 more Smart Citations
“…Previous studies have shown that p62 localizes to protein aggregates in many neurodegenerative diseases including SCA3 and may play a protective role in autophagic clearance of polyglutamine disease proteins. 28,29,41,42 By immunoblot analysis, diencephalic and cerebellar p62 expression levels did not differ across vehicle-treated WT, vehicle-treated Q84/Q84, or ASO-5-treated mice (see Fig 7C, E, F, H). We did, however, observe small, nuclear p62-positive puncta in the pons of Q84/Q84 vehicle-treated mice at 16 weeks of age, which were nearly absent in vehicle-treated WT or ASO-5-treated Q84/Q84 mice (see Fig 7B).…”
Section: Aso-5 Reverses Slowed Firing Frequency In Sca3 Purkinje Neuronsmentioning
confidence: 84%
“…pons, olivary nuclei, vestibular nuclei, cranial nerve nuclei), we focused our biochemical analysis on diencephalic tissue 3,28,29 . By immunoblot analysis, ASO-5 significantly reduced diencephalic mutATXN3 expression in a dose-dependent manner, though all doses showed efficacy (p<0.05) (Fig 1B and 1C).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, we will not go into the discussion on the toxicity of aggregation. For instance, it is still unclear whether the presence of aggregates contributes to SCA2 pathology (Huynh et al, 2000), even though aggregates are found in affected brain areas (Pang et al, 2002; Seidel et al, 2016). Finally, we will highlight the role of chaperones in the aggregation process and include only studies that provide insight in direct interaction of chaperones with the polyQ proteins.…”
Section: Introductionmentioning
confidence: 99%